Network Journalism Practice In Multiplatform Context: Indonesian Regional Environmental Journalists’ Perspective - Agustina, Anna; Hussein, Adnan (2015)
This paper examines journalism practice of regional environmental journalist in network journalism scheme for multiplatform context in Indonesia. Regional journalists usually have direct exposed to environmental problems in Indonesia, but the authority, either related to environmental problems or news coverage dissemination, both situated in Jakarta office. Within the media conglomeration industry in Indonesia, these context led network journalism practice with the limitation access of credible news sources in regions, while demand of multiplatform context need more information to produce news coverage. This paper aims to explore how regional environmental journalist does their job within this limitation and demand context.